Nurse-patient and family communication during the COVID-19 health crisis - Arenas-García, Cristina; Mirón-González, Rubén (Revista Española de Comunicación en Salud, 2022)
Introduction: The World Health Organization (WHO) declared COVID-19 as a pandemic on 11 March 2020. It was a disease transmitted by airway emissions and the use of a mask was made mandatory to prevent the spread. Communication was affected, especially in the clinical setting. Objectives: To describe the communication between the nurse, the patient and the family during the COVID-19 health crisis in the international socio-health context. Methodology: Narrative review of publications of 2020 and 2021. The databases consulted were: Cuiden, PubMed, SciELO, Cochrane Library Plus, Scopus and Web of Science. Google Academic and the journals Paraninfo Digital and Revista Española de Comunicación en Salud were also consulted. Results: 26 articles have been obtained. Conclusions: The communication has been affected by the pandemic, especially the non-verbal one due to the use of masks. In addition, the limited time available to the nurse to establish a conversation with the patient has also had a negative impact. Given this, telemedicine has emerged as an alternative to face-to-face care.
Keywords: communication; coronavirus; COVID-19; family; hospital; interpersonal relation; nurse; patient